Babies, Bodies, and Buyers - Williams, Patricia J. (Columbia Journal of Gender and Law, 2016)
In the thirty-five years since I began my career in legal education, much about the status of women, gender and sexuality has changed. There are the obvious triumphs: more female students, faculty and deans—as well as more bathrooms for more kinds of people than just “men.” Life is less lonely now, and conversation more intersectional. There is more openness about LGBT issues. There is marriage equality, however contested. And there is less general tolerance for open forms of harassment.